SISTEM INFORMASI PENJUALAN BERBASIS WEBSITE PADA CATERING DAPUR LUGTY - Gabriella Kristyawardani Putri (2023)
Based on The Use of Information and Communication Technology survey held by KOMINFO in 2017, 60% of respondents agrees that technology can increase work productivity, expand market opportunities, and obtain various information. And website is one of the technological media that 50.5% is used when Indonesians are connected to the internet (KOMINFO, 2017). Based on that survey, researcher build a sales information system for Dapur Lugty catering. The sales information system at Dapur Lugty catering can be a media campaign, streamline sales transactions and centralize sales transactions at Dapur Lugty catering. This research uses the waterfall method. The waterfall method was chosen because the requirements of the sales information system are clear and the possibility of requirements changes are small. This system is built with PHP and MYSQL. The result of this research is a sales information system that can be used by customers of Dapur Lugty catering to find out the price of the menu in Dapur Lugty, and do a sales transaction. After the website is done, researcher does a blackbox testing to make sure the system is running as planned. This system can also be used by catering owners to be able to manage sales transactions and payment transactions in Dapur Lugty catering.